A problem of extreme decomposition of the complex plane with free poles - Bakhtin, A. K. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.54 We study a problem of nonoverlapping domains with free poles on radial systems. Our main results strengthen and generalize several known results obtained in the investigation of this problem.